Kajian Alternatif Pemeliharaan Sungai Berdasarkan Kondisi Morfologi Kali Sumber Pinang Pasuruan - Felix Nova Ramadhan; Vita Ayu Kusuma Dewi (Universitas Islam Raden Rahmat, Malang, 2025)
The Sumber Pinang River often overflows, especially in the rainy season due to the ability of the river's capacity to not be able to accommodate water discharge, causing flooding in Sidogiri Village, Pasuruan Regency every year. This study aims to determine the performance of rivers and river infrastructure, as well as the necessary maintenance actions on the Sumber Pinang River guided by the Circular Letter of the Directorate General of Water Resources No.05/SE/D/2016. This study uses primary data in the form of an inventory of the existing conditions of sumgai and river infrastructure, as well as secondary data in the form of technical drawings of rivers and unit prices of goods and services in Pasuruan Regency. The results of the study showed that the Sumber Pinang River had a performance value of 63.12 with the category of corrective maintenance actions. In a total of 8 observation point segments, the performance value is <50, namely at point 4, point 7, point 14, point 48 and requires maintenance actions in the rehabilitative category. Priority improvements are in the form of normalization of rivers and repair of river embankments in the form of earthen embankments and parapets. The total maintenance cost on the Sumber Pinang River was obtained as Rp 23.670.546.185.